A ROS2-Based Robotics Course for Undergraduate Program - Pinto, Milena F.; Carvalho, Lucas L.M.; Sousa, Lucas C.; Amorim, Johann S.J.C.C; Nascimento, Yuri S.; Castro, Gabriel G. R. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
As the field of robotics continues to expand and influence various sectors, it becomes increasingly important to prepare engineering students to work with modern robotic systems. Practical knowledge and real-world experience are essential components in developing these skills. To bridge the gap between theory and practice, this paper presents a structured undergraduate course that introduces students to the Robot Operating System version 2 (ROS 2) using simulation-based and hands-on learning activities. Based on official ROS documentation and tools such as Gazebo and MAVROS, the course guides students through the foundational concepts of robotic control, embedded systems, robot modeling, and autonomous navigation. Each class is designed to progressively build technical skills while reinforcing theoretical understanding through project-based tasks. The primary goal is to enhance the comprehension of robotics topics by introducing a more hands-on and experimental learning environment. This kind of course equips students with computational tools, thereby significantly contributing to their hands-on experience in robotics.